A Preliminary Study on Adoption of SMS Banking Among Customer's in Libya - Algol, Mohammed Omar Ahmed (2010)
Banking has always been a highly information intensive activity particularly over the last few decades that information and Communication technology (ICT) has affected the banking industry heavily. The appearance of SMS banking services has changed the nature of financial services delivery costumers. One of the most growing phenomenon's in financial services is mobile internet banking. The purpose of this study is explorer the adoption of SMS banking among Libya customers, an emerging Middle East economy in the area. The present study modifies the technology acceptance model and applies it to banks customers in Libya. By providing SMS banking services, banks can get notable cost saving, reduce their branch networks, and improve efficiency. But since customers do not adopt and use these service, banks cannot profit from them. A numbers of Libya banks recently have started to offer SMS banking services to their customers, but the fact it got a respectable reaction from people' point of view. A model of TAM with factors from perceived innovation attributes and the personal characteristics of adopters have been developed to identify the most factors that influence SMS banking adoption among Libya customers. Also I used this section describes the research methods used to test the hypothesis developed based on the Theory of technology acceptance model (TAM) as the underpinning theory to the SMS Banking Adoption. The result of this study were contribute were positively related to SMS banking adoption as hypothesized. The positive association between combination among all independent variables (ease of use, usefulness, credibility, compatibility and observability) was supported.